Sistem Pendukung Keputusan Pemilihan Supervisor Terbaik Menggunakan Metode GAP Analysis - Panjaitan, Hanna Yoseva (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
In selecting the best supervisor at PT. Lintas Nusantara Access is determined based on the value obtained from each criterion determined by the company. However, there are quite a lot of supervisor candidates who meet the criteria for selecting the best supervisor. Apart from that, the selection carried out previously was considered less effective considering that the system used was not yet computerized, resulting in the assessment process in selecting the best supervisor being less than optimal and taking a long time. With the existing problems, it is necessary to conduct an assessment using the Decision Support System (DSS) application to assist in decision making in determining the selection of the best supervisor more precisely and quickly, then analyzed using the gap analysis method to determine the ranking based on the value of the final results of alternatives (employees) . This research produces a Decision Support System (DSS) application for selecting the best supervisor using Microsoft Visual Studio and MySQL tools as a database. So selecting the best supervisor at PT. Lintas Nusantara Access will be more effective and computerized so that it can help avoid conditions occurring in the best supervisor assessment process.